A regional cooperative clinical study of radiotherapy for cervical cancer in east and south-east Asian countries - Takashi Nakano (2018)
Purpose: Radiotherapy differed widely in east and south-east Asia because of technical, cultural, and socio-economic differences. With the purpose of standardizing radiotherapy for cervical cancer in the region, an international clinical study was conducted. Materials and methods: Eleven institutions in eight Asian countries participated in the study. Between 1996 and 1998, 210 patients with stage IIIB cervical cancer were enrolled. Patients were treated with a combination of external beam radiotherapy (total dose, 50 Gy) and either high-dose-rate (HDR) or low-dose-rate (LDR) intracavitary brachytherapy (ICBT) according to the institutional practice. The planned point A dose was 20-28 Gy/4 fractions for HDR-ICBT and 30-40 Gy/1-2 fractions for LDR-ICBT. Results: Hundred patients were treated with HDR-ICBT and 110 were treated with LDR-ICBT. The ICBT doses actually delivered to point A ranged widely: 12-32 Gy in the HDR group and 26-52.7 Gy in the LDR group. The 5-year follow-up rate among the countries differed greatly, from 29% to 100%. The 5-year major complication rates were 6% in the HDR group and 10% in the LDR group. The 5-year overall survival rates were 51.1% in the HDR group and 57.5% in the LDR group. Conclusions: Although there were several problems with treatment compliance and patients' follow-up, the study suggests that the protocols provided favorable outcomes with acceptable rates of late complications in the treatment of advanced cervical cancer in east and south-east Asia. © 2007 Elsevier Ireland Ltd. All rights reserved.